Science that Swears by Objectivity is Half-Blind - Padmanabhan, Vijayaraghavan (International Journal of Innovative Research in Medical Science, 2024)
Whatever is deemed to be objective, is in the final analysis, the subjective opinion of an individual. Thus science, by its very origin, has a subjective element. Common sense allows a balanced approach, where objectivity and subjectivity are treated equally without any bias. Even mathematical equations that appear objective, have a subjective element, the classic example being the equations of quantum mechanics. Focusing within the boundaries formed by objectivity, subjectivity and common sense can be the basis for a methodology that allows intuition and creativity to express themselves. There are enough reasons to consider objectivity and subjectivity on an even scale. Great scientific discoveries have been made based on intuition (which is subjective), that has been further pursued with objectivity and common sense.